ANALISIS FAKTOR INTERNAL DAN EKSTERNAL KESULITAN BELAJAR MATEMATIKA KELAS V - Jayanti, Indriani; Arifin, Nurdin; Rahman Nur, Dedi (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2020)
The purpose of this study was to determine the learning difficulties Mathematics experienced by students. This type of research is qualitative research with a subject of 16 students who have difficulty learning Mathematics. The results of this study showed that: 1) internal factors of mathematics learning difficulties experienced by students in VD grades are the interest factors of students' learning, motivational factors and attitudes of students, and student learning habits. An internal factor that does not affect VD students in math learning difficulties is sensing ability. 2) External factors of mathematics learning difficulties experienced by students in VD class are teaching methods of teachers, and learning facilities. External factors that do not affect students in VD class who have difficulty learning Mathematics is the teacher's relationship with the student.